Discipline and punish : the birth of the prison - Foucault, Michel (Vintage Books, 1995)
In this brilliant work, the most influential philosopher since Sartre suggests that such vaunted reforms as the abolition of torture and the emergence of the modern penitentiary have merely shifted the focus of punishment from the prisoner's body to his soul.